International Encyclopedia of the Social &Amp; Behavioral Sciences 2015
DOI: 10.1016/b978-0-08-097086-8.74028-1
|View full text |Cite
|
Sign up to set email alerts
|

Planning During Post-Socialism

Abstract: This article analyzes the state of public sector planning in countries that subscribed to a Marxist, state-socialist ideology during some part of the twentieth century, and especially those countries that comprise the former Eastern Bloc (today often referred to as the 'transitional countries'). Central economic planning was a defining feature of state socialism. With its collapse, this type of planning was abandoned. During the early years of postsocialism, all types of public sector planning, including urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Uncontrolled urban expansion is perceived as a negative way of development [4,94], in and of itself. It is stimulated by the fast pace of transformations, illustrating the lack of proper planning, characterized by ad-hoc decisions [5,67,68] without coordination between different projects [111], which all lead, more often than not, to a patchwork of spatial arrangements. One of the most visible results is the lack of clear functional zoning that fosters a heterogeneous mixture of residential (single-family houses or multi-family residential complexes) and non-residential areas (commercial, logistical, high-rise offices, industrial, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled urban expansion is perceived as a negative way of development [4,94], in and of itself. It is stimulated by the fast pace of transformations, illustrating the lack of proper planning, characterized by ad-hoc decisions [5,67,68] without coordination between different projects [111], which all lead, more often than not, to a patchwork of spatial arrangements. One of the most visible results is the lack of clear functional zoning that fosters a heterogeneous mixture of residential (single-family houses or multi-family residential complexes) and non-residential areas (commercial, logistical, high-rise offices, industrial, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies revealed that the CEE city regions are generally characterized by a more dispersed pattern of development than Western Europe [52,56] in view of higher rates of urban growth [65]. The main challenges are the inefficient policies and loose regulatory framework [66,67] that foster an uncontrolled development of built-up areas in the vicinity of large cities [56,68].…”
Section: Introductionmentioning
confidence: 99%
“…The close cooperation between the private sector and governmental bodies also started to flourish in the spatial planning domain [99], bringing about a neoliberal planning paradigm labeled as the investor urbanism. It refers to a developer-led versus public-led planning practice that adapted and subordinated urban space to the dictates of capital, pushing the public interest into the background [100][101][102]. Its mechanisms were simple-they involved either the ad-hoc adoption of new plans and amendments to the existing ones, with modifications introduced to match the investors' needs [100,103] (pp.…”
Section: Context Of the Delayed Transitionmentioning
confidence: 99%
“…18 Andrusz, Harloe, Szelenyi 1996Benkő, Kissfazekas 2019;Dmitrieva, Kliems 2010. 19 Hirt, Stanilov 2009Hirt 2015;Van Assche, Verschraegen, Salukvadze 2010;Tsenkova 2007. 20 The research conducted within the frame of international network "Legacies of The present paper outlines a number of ways, in which architects and urban planners have described reconnecting their professional field with other significant spaces and chronologies.…”
Section: Introductionmentioning
confidence: 99%